Is the role of Coronectomy procedures expanding? - Parmanand Dhanrajani (Elsevier, 2021)
Aim or purpose: Extractions of lower third molars carry risk to the inferior alveolar nerve (IAN), varying from 0.42% to 7.8%. Risk varies between the operating skills of individuals. The cost of medicolegal litigation settlement in these cases have been sky rocketing.Coronectomy is an alternative procedure increasingly accepted world-wide to reduce the risk of nerve injuries. Increasing use of cone beam computed tomography (CBCT) aids assessment of the relationship of the IAN and roots in providing treatment planning to reduce the risk of nerve trauma. Materials and methods: This retrospective study presents, patients who underwent coronectomy from 2012-2020 and analyses the post-coronectomy pain, migration of roots and follow-up of patients with comorbidities and/or decayed teeth. Results: A total of 5,497 lower third molars were removed. In the cohort of 1,543 (28.06%) teeth removed in outpatient under local anaesthesia, 109 (1.98%) were coronectomies and of 3,954 (71.93%) removed under general anaesthesia, 305 (5.54%) were coronectomies. Conclusion: The outcome of this study demonstrates:● coronectomy is a safe and viable technique for the surgical management of wisdom teeth at high risk of neurosensory loss.● Intra pulpal deposition of local anaesthetic intraoperatively reduced the post coronectomy pain significantly.● The modification in surgical technique does reduce the post-surgical complications such as wound dehiscence.● Migration of roots does occur but to quantify the amount is challenging.● Follow-up results with patients with comorbidities and decayed teeth are encouraging and wider acceptance need to be seen in future.